The Impact of Child Custody Laws on Child Well-being: A Comparative Study - Dewi Larasati; Andi Prasetya; Rizky Fitriani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study examines the influence of child custody laws on child well-being in post-divorce families. By comparing legal frameworks across countries, the research assesses the outcomes of different custody arrangements concerning children’s psychological health, academic performance, and social stability. Findings indicate that shared custody generally provides better well-being outcomes for children, although cultural and legal variations affect these impacts.